Students’ Mathematical Literacy Skills Through Contextual Teaching and Learning and Problem-Based Learning Models - Sofyan, Deddy; Puspitasari, Nitta; Maryani, Siti (Department of Mathematics Education Program IPI Garut, 2025)
Kemampuan literasi matematis siswa merupakan salah satu kemampuan kognitif yang penting untuk dikuasai oleh siswa. Berdasarkan PISA 2022 menunjukkan Indonesia masih tergolong rendah. Tujuan penelitian untuk mengetahui apakah ada perbedaan kemampuan literasi matematis siswa antara siswa yang mendapatkan model Contextual Teaching and Learning (CTL) dan Problem Based Learning (PBL). Metode yang digunakan dalam penelitian ini adalah kuasi eksperimen dengan populasi yaitu siswa SMP kelas VIII pada salah satu sekolah di kabupaten Garut. Teknik pengambilan sampel pada penelitian ini adalah purposive sampling. Teknik pengumpulan data yang digunakan yaitu tes dan observasi. Teknik analisis data menggunakan uji t dan gain ternormalisasi. Hasil penelitian ini yaitu: Terdapat perbedaan kemampuan literasi matematis siswa antara yang mendapatkan model CTL dan PBL; Kualitas peningkatan kemampuan literasi matematis siswa kelas CTL termasuk pada kategori sedang; Kualitas peningkatan kemampuan literasi matematis siswa kelas PBL pada materi termasuk pada kategori sedang. Students' mathematical literacy skills is one of the important cognitive skills that students need to master. According to PISA 2022, Indonesia is still categorized as having a low level of performance. The purpose of this study is to determine whether there is a difference in students' mathematical literacy abilities between those who received the Contextual Teaching and Learning (CTL) model and those who received the Problem-Based Learning (PBL) model. The method used in this study is a quasi-experiment with the population being 8th-grade junior high school students at a school in Garut Regency. The sampling technique used in this study is purposive sampling. The data collection techniques used are tests and observations. Data analysis techniques include the t-test and normalized gain. The results of this study are: There is a difference in students' mathematical literacy skills between those who received the CTL model and those who received the PBL model; The improvement in mathematical literacy skills of students in the CTL class is in the medium category; The improvement in mathematical literacy skills of students in the PBL class is also in the medium category.